АНАЛІЗ ЗМІНИ ЧАСТОТИ В ОЕС УКРАЇНИ ЗА РІЗНИХ РЕЖИМІВ ЇЇ РОБОТИ - Кириленко , О.В.; Павловський, В.В.; Стелюк, A.O.; Леньга, О.В.; Зайченко, В.Б.; Лиховид, Ю.Г. (Інститут електродинаміки НАН України, Київ, 2023)
The article presents the main analysis results of the frequency change in the interconnected power system (IPS) of Ukraine under the conditions of its isolated operation, as well as synchronous operation with the UPS/IPS and ENTSO-E. The reasons for the change in the maximum and minimum values are considered, as well as the frequency histograms for the above modes of operation of the IPS of Ukraine are presented. References 5, tables 1, figures 7.